Prevalência dos marcadores sorológicos dos vírus das hepatites B e D na área indígena Apyterewa, do grupo Parakanã, Pará, Brasil - NUNES, Heloisa Marceliano (2014)
In order to study the prevalence of hepatitis B (HBV) and D (HDV) viruses in the Parakanã Indians and to evaluate the impact of hepatitis B vaccination beginning there in 1995, 258 serum samples were analyzed in the year 2004 for hepatitis B and D serological markers using immunoenzymatic techniques; the results showed a moderate endemic pattern, with a total prevalence of HBV infection of 55.7% and 5.4% of virus carriers in the Apyterewa village and 49.5% with 1.1% of HBV carriers in the Xingu village; 31.4% of anti-HBs+ as an isolated marker in both villages and no detection of positive serological tests for HDV among HBV carriers. The laboratory analysis thus showed the presence of chronic HBV carriers, absence of HDV carriers, and an emerging vaccine profile among susceptibles, confirming the effectiveness and need to maintain vaccination, especially in the first year of life, and the need to implement effective epidemiological surveillance for early detection of HDV infection among HBV carriers.